2022
DOI: 10.1093/mnras/stac876
|View full text |Cite
|
Sign up to set email alerts
|

Is the orbital distribution of multiplanet systems influenced by pure three-planet resonances?

Abstract: We analyse the distribution of known multi-planet systems (N ≥ 3) in the plane of mean-motion ratios, and compare it with the resonance web generated by two-planet mean-motion resonances (2P-MMR) and pure 3-planet commensurabilities (pure 3P-MMR). We find intriguing evidence of a statistically significant correlation between the observed distribution of compact low-mass systems and the resonance structure, indicating a possible causal relation. While resonance chains such as Kepler-60, Kepler-80 and TRAPPIST-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In such a model, some planet pairs are "near-resonant" only coincidentally (reaching that state after the dissipation of the protoplanetary disk) and not as the consequence of resonant capture or damping. The actual fraction of systems that never experienced a post-gas instability in the overall sample is unclear: Izidoro et al (2021) suggest that no more than 5% remain stable and resonant, but it remains to be seen whether those results are consistent with the overabundance of threebody libration seen in the Kepler sample (Goldberg & Batygin 2021;Cerioni et al 2022). While basic modeling of the peaks in the period ratio distribution has had some success (e.g., Choksi & Chiang 2020;Ghosh & Chatterjee 2023), the results of this work illuminate a novel and stringent constraint that must be accounted for in a complete model of planet formation.…”
Section: Discussionmentioning
confidence: 99%
“…In such a model, some planet pairs are "near-resonant" only coincidentally (reaching that state after the dissipation of the protoplanetary disk) and not as the consequence of resonant capture or damping. The actual fraction of systems that never experienced a post-gas instability in the overall sample is unclear: Izidoro et al (2021) suggest that no more than 5% remain stable and resonant, but it remains to be seen whether those results are consistent with the overabundance of threebody libration seen in the Kepler sample (Goldberg & Batygin 2021;Cerioni et al 2022). While basic modeling of the peaks in the period ratio distribution has had some success (e.g., Choksi & Chiang 2020;Ghosh & Chatterjee 2023), the results of this work illuminate a novel and stringent constraint that must be accounted for in a complete model of planet formation.…”
Section: Discussionmentioning
confidence: 99%
“…The offsets observed in several planetary systems with respect to 2P-MMRs (e.g., Kepler-80, TOI-178) appear consistent with such an evolutionary route (e.g., MacDonald et al 2016;Leleu et al 2021), perhaps indicating that the resonant structure of small-mass planetary systems could have a stronger correlation to 3P-MMRs than to two-planet commensurabilities (Cerioni et al 2022). However, in no case was a capture reported in a first-order three-planet resonance, nor was such a configuration suggested as an evolutionary route due to tidal effects.…”
Section: Tidal Evolution Of the Six-planet Chainmentioning
confidence: 71%
“…Direct tidal interactions between the other planets and the star proved negligible, and thus their tidal parameters could not be constrained. Surprisingly, even the current offset of the outer pair n f /n g ; 3.3 can be explained by tidal evolution alone, indicating that perhaps other seemingly nonresonant systems may be dynamically affected by two-planet or three-planet commensurabilities, even more so than previously thought (e.g., Cerioni et al 2022).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, Cerioni et al (2022) analyzed from a statistical point of view the correlation between the observed distribution of compact low-mass multi-planet systems and the 2-and 3planet resonant structures and showed evidence in favor of a correlation with 3-planet resonances, which could be statistically explained by tides. Note also that the survival of Laplace-like resonances with tidal effects was newly investigated by Celletti et al (2021) for the satellite case (where the tides act in a different manner since the planets orbit a usually slow-rotating central star while the satellites orbit a fast-rotating central planet).…”
Section: Introductionmentioning
confidence: 99%